BIM in principle and in practice - Barnes, Peter 1954-; Davies, Nigel (Institution of Civil Engineers Publishing, 2014)
This new book will enable you to answer the questions: what is BIM?; how can I apply it in practice?; and how could it develop in the future at both practical and legal levels?. Relevant to all companies and projects, whatever their size and geographical market, the up-to-date advice and illustrative case studies within this book forms the ultimate practical guide to current practice and a valuable vision for the future